ROLE OF THE KAREN JEPPE ARMENIAN COLLEGE IN PRESERVING THE ARMENIAN IDENTITY OF THE COMMUNITY (EDUCATION IN THE 21ST CENTURY, 2023)
The postgenocidal diaspora is over 100 years old. For a century, all educational institutions ofthe diaspora, without exception, have tried to build their identity in new conditions. They built achurch, a school, cultural and trade union institutions, organizations in their midst and became239Armenian communities, where a new life for the Armenian diaspora that survived the genocidewas born.This article discusses the activities of the National Karen Yeppe Jemaran in Aleppo since1947 to preserve the Armenian identity and national education of the community, noting thatJemaran is the only secondary school where 100% of the students are Armenian.
Keywords: Aleppo, national school, preservation of Armenian identity, national education, Western Armenian, Armenian school mission, colony.